The Effect Of Personal Types On The Performance Of Employees In Petapahan Lubuk Pakam Office - Devi Amanda Putri (Junal Ilmu Manajemen, 2020)
This type of research uses associative research, namely population There are 39 employees who work in Petapahan Lubuk Pakam Village. The sampling is done by using saturated samples, so the number of research samples is 39 respondents. Sources of research data using primary data and secondary data, data collection techniques using literature study, questionnaires and observations. The data analysis technique used validity and reliability tests, simple linear regression, classic assumption tests and hypothesis testing. Based on the results of the study, it shows that partially personality has a positive and significant effect on employee performance in Petapahan Lubuk Pakam Village. Employee personality has a strong correlation with employee performance, and personality can explain employee performance by 50.2%, and the remaining 49.8% can be explained by other variables such as training, compensation, career development, and so on